Study for Necessity - Kwiatek, JoEllen, 1957- (Book collections on Project MUSE., 2015)
"Study for Necessity is the 2014 winner of the Iowa Poetry Prize. Judge Emily Wilson: Kwiatek's poems emit the uncanny luminosities of the artists' worlds they refer to: those of Casper David Friedrich, Albert Pinkham Ryder, and Odilon Redon. Each is a "token of strangeness" built with delicacy and restraint, embodying, vivifying, what the poet calls the mind's "lonesome flourish""--